2016
DOI: 10.7585/kjps.2016.20.3.189
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Multifunctional Bacillus sp. GH1-13

Abstract: Several microorganisms in particular Bacillus subtilis group have been isolated from diverse places such as soils and the gastrointestinal tract of ruminants etc., and used as biocontrol agent against various plant pathogens and utilized as plant growth promoting agents. Among them, Bacillus is well known as one of the most useful bacteria for biocontrol and plant growth promotion. Bacterium GH1-13 was isolated from a reclaimed paddy field in Wando Island and identified as Bacillus velezensis using phylogeneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 19 publications
0
12
0
6
Order By: Relevance
“…thaliana and rice seeds soaked in a solution containing YxaL in the sub-nanomolar range (0.1 ~ 1 mg L -1 ) showed a significant improvement with respect to root growth as did treatment with B . velezensis GH1-13 cells [9]. A previous study showed that the use of bovine serum albumin (BSA) as an organic N-source supplement produced similar effects on the root growth and development of A .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…thaliana and rice seeds soaked in a solution containing YxaL in the sub-nanomolar range (0.1 ~ 1 mg L -1 ) showed a significant improvement with respect to root growth as did treatment with B . velezensis GH1-13 cells [9]. A previous study showed that the use of bovine serum albumin (BSA) as an organic N-source supplement produced similar effects on the root growth and development of A .…”
Section: Discussionmentioning
confidence: 99%
“…velezensis strain GH1-13 was isolated from rice paddy soil in Korea and can promote plant growth and suppress several pathogens [8]. This strain was shown to produce indole 3-acetic acid (IAA) associated with promoted growth of rice root [9]. The chromosome sequence of strain GH1-13 (GenBank accession number CP019040.1) contains highly homologous genes responsible for the biosynthesis of some plant hormones and secondary metabolites, such as IAA, 2,3-butanediol, non-ribosomal lipopeptides, and polyketide antimicrobials, which are believed to be more proficient for rhizosphere colonisation and pathogen control than other members of the B .…”
Section: Introductionmentioning
confidence: 99%
“…One μl of the bacterial suspension was subjected to a template for PCR. Primer pairs demonstrated in Kim et al (2016) for the six antimicrobial peptide biosynthetic genes were used. PCR amplifications were carried out in 50-μl reaction mixture.…”
Section: Methodsmentioning
confidence: 99%
“…were obtained using options according to the Kimura twoparameter model (Kim et al, 2016;Kimura, 1980), and clustering was performed using the Neighbor-Join algorithms (Saitou and Nei, 1987) to a pairwise matrix, which was inferred by using the maximum composite likelihood method, with a 1,000-replicate (Felsenstein, 1985) bootstrap test using MEGA 7. The phylogenetic tree was drawn to scale, with the branch lengths measured by the number of substitutions per site.…”
Section: Methodsmentioning
confidence: 99%
“…A molecular phylogenetic tree based on the amino acid sequence of the 16S rRNA gene of the AFB2-2 strain was performed automatically using the MEGA version 7 ( Kumar et al, 2016 ) after multiple alignments of the data with the CLUSTAL W ( Thompson et al, 1994 ). Distances were obtained using options according to the Kimura two-parameter model ( Kim et al, 2016 ; Kimura, 1980 ), and clustering was performed using the Neighbor–Join algorithms ( Saitou and Nei, 1987 ) to a pairwise matrix, which was inferred by using the maximum composite likelihood method, with a 1,000-replicate ( Felsenstein, 1985 ) bootstrap test using MEGA 7. The phylogenetic tree was drawn to scale, with the branch lengths measured by the number of substitutions per site.…”
Section: Methodsmentioning
confidence: 99%